OptimationStudy of Processing Technology of Instant Corn Grits - Sugiyono .; Soewarno T Soekarto; Purwiyatno Hariyadi; Agus Supryadi (Jurnal Teknologi dan Industri Pangan, 2004)
This research was aimed to process corn kernels into instant corn-grits. Corn kernels were milled into grits and pregelatinized before drying to make them instant product. The study showed that pre-gelatinization step affected the degree of gelatinization of corn-grits, which inturn significantly affected characteristics of the product such as cooking time, degree of swelling and amount of water absorbed. Processing of corn kernels into instant corn-grits yielded 60 – 63% product. Instant corn grits can be cooked for 5 minutes. The shelf life of the product lasted for 12.8 – 13.4 months. Key words : Pre-gelatinization, instant, corn-grits.